Experimental study for synthesization and characterization of porous adsorbents for cooling and gas storage applications - Soh, Michael Wai Kit (Nanyang Technological University, 2023)
Renewable energy driven cooling and desorbing gas are essential to mitigate the emission of carbon dioxide (CO2) into the atmosphere. The adsorption bed consisting of finned-tube heat exchanger and porous adsorbents, is the main component of an adsorption device. The efficacy factor of an adsorption bed is determined by the adsorbate loadings on the porous adsorbents. Therefore, the design and synthesisation of adsorbents is an important research area. Generally, zeolites, activated carbon, fibres and silica gel are used as adsorbents to fabricate the bed heat exchanger. Currently, metal-organic frameworks (MOFs) are found promising for gas adsorption, separation and heat transformation applications. Another research area lies in the development of MOFs. For example, functionalized UiO-66(Zr), Aluminium Fumarate and CAU-10 MOFs are suitable for applications involving heat transformation. On the other hand, HKUST-1 and MIL-101(Cr) are found promising for H2 adsorption and storage at 77 K and CO2 at room temperature. This project focus mainly on the synthesisation and characterization of functional MOFs for water and CO2 adsorption. At first, the parent MOFs namely HKUST-1 and CAU-17 are synthesised using solvothermal method (at 120 °C for 12 hours). Secondly, both parent MOFs are modified employing BMIMCL and Piperazine (Pz) as modified linker. The surface properties of these MOFs are measured by 1) thermos-gravimetric analyzer (TGA) for measuring the thermal stability and 2) scanning electron micrography (SEM) for the morphology. The TGA allows to determine the decomposition temperature and water desorption rate of the MOFs. The decomposition temperature of HKUST-1, HKUST-1 BMIMCL 1:1 and HKUST-1 BMIMCL 1:2 is approximately 275 °C. CAU-17 and CAU-17(Pz) show a higher decomposition temp of 400°C. The SEM images of the MOFs show that incorporation of BMIMCL and Pz in MOFs results in significant morphological change. The isotherms for water and CO2 adsorption are shown, which are essential for the design of gas storage chamber or thermal compressor.